Dumped through Technology: A Policymaker's Guide to Disenfranchising Slum Dwellers. (July 2013) - Chandola, Tripta
This article critically examines the position of slum-dwellers as citizens and the entitlements available to them within the transforming urban materiality of Delhi. By undertaking a detailed analysis of the media reportage of the recently released 'Housing Stock, Amenities & Assets in Slums—Census 2001', this article argues that there is a systemic and strategic shift in the imagination of 'marginalized' groups—here, namely the slum dwellers—as 'citizens', which significantly limits their 'right to the city'. Within this imagination there is a deliberation to consider the 'marginalized' groups as proactive 'consumers', such that 'amnesia of the experience of poverty', is sustained by situating their position as citizens within the topos of their media consumption practices and trends. This article draws upon decade long ethnographic research in the slums of Govindpuri, which is highlighted as a case study. It attempts to situate the shifting position of the 'marginalized' groups as 'citizens' determined within the particular and peculiar logic of neo-liberalism in developing countries wherein 'cleanliness' not only becomes a state of being but essential to 'being' a part of the State. The article particularly emphasizes on the deliberately 'diminishing' role the State intends to play in the welfare of the 'marginalized'.